Students’ Attitudes towards the War in Ukraine - Huszti Ilona; Густі Ілона; Ielyzaveta Baran; Bárány Erzsébet; Барань Єлизавета; Fábián Márta; Фабіян Марта (H. S. Skovoroda Kharkiv National Pedagogical University, 2024)
Abstract. Purpose. Our research has been conducted in a region of Ukraine where no direct military operations have occurred since 24 February 2022. However, we have been living in the shadow of the horrible ongoing war; regular air raid alarms have had negative impacts on people who feel mental constraints: uncertainty, anxiety, anger, despair, disillusionment, and often hopelessness. Thus, the primary aim of our survey was to get deeper insights into the feelings and attitudes of our students towards the war in order to help them process the situation they have been living in. Methodology. We have applied the quantitative research method in our study. We designed an online questionnaire using Google Forms with sixteen 16 Likert-scale-type questions. It was administered online to college students aged 17–24, having 17 different majors. Altogether 194 questionnaires were completed and returned during February and April 2023. Descriptive statistics were calculated with the objective of providing a clear and concise summary of the data that would allow us to gain insights into the main topic under consideration, as well as to understand patterns emerging within the data. Results. The findings suggested that students were mostly worried about the outcomes of the war. Students were rather informed about the happenings of the war, although about a third of the respondents claimed they did not follow the daily news from the front. A large majority of research participants were optimistic about the fast and positive ending of the war in spring 2023. In contrast, only approximately a third of the students were absolutely positive about the future of their native land after the end of the war. Conclusions. Overall, it can be stated that the students’ attitudes towards the war were rather optimistic. It is two years now that the war has been going on. The initial optimism of our students concerning the outcomes of the war must have changed during this time. Therefore, as a further research direction, a cross-sectional study is due to be performed in which we trace the shift in attitudes of our students towards the war in Ukraine and compare and contrast them with previous results.

Резюме. Дослідження проводилось в одному з регіонів України, де з 24 лютого 2022 року не ведуться безпосередні бойові дії. Однак ми живемо в умовах жахливої війни, яка й надалі триває, з регулярними повітряними тривогами, що негативно впливають на людей і спричиняють важке психічне навантаження: невпевненість, тривогу, злість, відчай, зневіру, розчарування, безнадійність. Таким чином, основною метою нашого опитування було глибше зрозуміти почуття і ставлення здобувачів вищої освіти нашого закладу до війни для того, щоб допомогти їм впоратися з ситуацією, в якій вони опинилися. Методологія. У дослідженні застосовано кількісний метод дослідження. В якості знаряддя дослідження розроблено онлайн-анкету з використанням Google Forms з шістнадцятьма питаннями типу шкали Лайкерта. Опитування проводилося у форматі онлайн серед здобувачів закладу вищої освіти віком від 17 до 24 років, які навчаються на сімнадцяти різних спеціальностях. Загалом було заповнено 194 анкети протягом лютого-квітня 2023 року. Описову статистику використано з метою чіткого і стислого узагальнення даних, що дозволило отримати глибше розуміння основної теми, а також зрозуміти закономірності, що випливають із цих даних. Результати. Результати дослідження показали, що студентів найбільше турбують наслідки війни. Вони досить поінформовані про хід війни, хоча близько третини респондентів стверджували, що не слідкують за щоденними новинами про ситуацію в державі. Переважна більшість учасників дослідження були оптимістично налаштовані навесні 2023 року щодо швидкого та позитивного завершення війни. На противагу цьому, лише близько третини студентів були абсолютно позитивно налаштовані щодо майбутнього своєї рідної країни після закінчення війни. Висновки. У цілому можна зазначити, що переважна більшість респондентів оптимістично налаштовані щодо майбутнього. Початковий оптимізм респондентів стосовно наслідків війни за цей час очевидно змінився. Тому в якості подальшого напрямку дослідження заплановано проведення дослідження поперечного перерізу, в якому ми могли б простежити зміни у ставленні наших студентів до наслідків війни в Україні та зіставити їх з попередніми результатами.
Ставлення студентів до війни в Україні
Редакційна колегія: https://educationalchallenges.org.ua/index.php/education_challenges/about/editorialTeam
Зміст: https://educationalchallenges.org.ua/index.php/education_challenges/issue/view/12
Keywords: College Students; Distance Learning; Online Teaching; Students’ Attitudes to the War; Transcarpathia; War in Ukraine; війна в Україні; дистанційне навчання; Закарпаття; онлайн навчання; ставлення студентів до війни; студенти закладу вищої освіти